Insomnia During The COVID-19 Pandemic and Its Relationship with Psychological Distress in Health Workers: A Literature Review - Yullytia Franika Maryati; Ross James Godwin; Saiful Hidayat (Magna Neurologica, 2023)
Background: The global COVID-19 pandemic has had a significant impact on all aspects of daily life. One area it has impacted is psychological stress experienced by health workers, particularly sleep disorders. Insomnia is frequently related to stressful situations, such as the current COVID-19 pandemic crisis and other mental health-related work. The development of sleep disorders such as insomnia may affect the well-being of healthcare workers. Objective: This literature review aims to summarize the evidence concerning insomnia during the COVID-19 pandemic and its relationship to psychological distress in healthcare workers and to detect associated stress symptoms with sleep quality in health workers. Methods: This literature review searched PubMed and ScienceDirect for articles (2020–2022) on insomnia during COVID-19 and its link to psychological stress. The review followed PRISMA guidelines. Results: A total of five articles were analyzed. Three studies indicated that insomnia was associated with stress symptoms even with low exposure to COVID-19 patient care. Two other articles showed that psychological distress has a negative impact on sleep quality to such a level that it interferes with daily activities. Conclusion: Sleep disorders, including insomnia, are related to psychological distress in health workers in the COVID-19 pandemic era. Providing social and psychological support to health workers is crucial because the emotional well-being of health workers affects the quality of patient care and, subsequently, the effective functioning of health services.